Legal framework on the enforceability, fairness and data protection surrounding the electronic transaction: a case of Malaysia - Zulhuda, Sonny (Graduate Study Atma Jaya School of Law, 2014)
More widely-connected people at both end of commerce facilitated by the Internet had formed a substantial global and regional marketplace. Malaysian business community is quickly grabbing this opportunity with an increasing popularity of electronic commerce and electronic transactions in the country. Legal and consumer issues submerge relating to issues of enforceability of electronic paperless contracts. The widespread unfair contractual terms quickly become another concern. Meanwhile, the massive use of personal data in e-transaction process has also presented new concerns in relation to the privacy and safety of the e-transaction. The Malaysian legal framework on enforceability of e-transaction, consumer protection over unfair terms and data privacy surrounding e-transaction has tremendously developed in the past few years with the enactment and amendment of relevant statutes. This paper discusses the development from legislative and judiciary perspectives and highlights some issues and concerns. It finds that the law in this area is arguably moving towards a right direction.